Poliuretanos e nanocompósitos biodegradáveis derivados de dispersões aquosas projetados para aplicações biomédicas - Eliane Ayres (2006)
Waterborne polyurethane (PUDs) with potential for application as biomaterial were synthesized. Polypropyleneglycol (PPG) and/or polycaprolactonediol (PCL) were used as soft segment. The hard segment was formed by extending isophorone diisocyanate (IPDI) with hydrazine (HZ) producing poly (urethaneurea) s. PUDs were reinforced with Na+-montmorillonite (Na+-MMT) and sodium bentonite to give nanocomposites (CPUDs). Here, water was used as swellingagent to make the basal space of silicate layers widen without any chemical treatment. PCL is a biodegradable aliphatic polyester, but the degradation rate of PPG/PCL based polyurethane was very slow. Poly(ethylene glycol) (PEG) enhanced hydrophilicity and caused an increase in water permeability as showed by hydrolytic tests. According to XRD curves, although the clay structure was present in some extent, asshowed by the presence of peaks, the obtained nanocomposites achieved some degree of intercalation. Small angle X-ray scattering (SAXS) results showed that the incorporation of inorganic species into PUDs yielded nanocomposites with nanocomponents intercalated to larger distances (25nm) characteristic of exfoliated nocomposites.To investigate the degree of hydrogen bonding and microphases mixing of the polyurethanes and nanocomposites, Fourier-transform infrared spectroscopy (FTIR) experiments were performed. The carbonyl absorption was split into two bands, and the relative absorbances of the two carbonyl bands, served as an index of the degree to which this group participates in hydrogen bonding. Structural parameters, obtained from mathematical manipulation of SAXS data showed that polyurethane based in polyester in its soft segment has longer inter-domain repeat distance (L) than that one based in polyether. Surprisingly, the degradation temperatures, examined by thermogravimetric analysis(TG), of PUDs, were almost the same of the nanocomposites (CPUDs). Differential scanning calorimetry (DSC) measurements showed that glass transition temperature (Tg) of CPUD can be lower or higher than that of the PUD. Mechanical tests performed in PUDs exhibited values of tensile strength and elongation at break up to 50Mpa and 1400% respectively. CPUD with 1% of MMT content demonstrated the best mechanical properties among the nanocomposites. Preliminary in vitro experiment has shown that polycaprolactone based polyurethane isbiocompatible with osteoblasts and these cells could adhere and proliferate on the material. Such biodegradable materials can find potential application as uniquely attractive biomedical polyurethanes.